2021
DOI: 10.1093/jee/toab224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Functional Characterization of Vitellogenin Receptor From Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Vitellogenin receptors (VgRs) have vital roles in reproduction by mediating endocytosis of the vitellogenin (Vg) in oviparous insects. Same as most insect species that possess only one VgR, in this study, a single VgR mRNA (HmVgR) was identified in an important natural enemy ladybeetle, Harmonia axyridis (Pallas). The open reading frame of HmVgR was 5,340 bases encoding a protein of 1,779 amino acids. Bioinformatic analyses showed that HmVgR had conserved domain motifs of low-density lipoprotein receptor famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…42 Similarly, the RNAi-mediated silencing of HmVgR blocked the deposition of yolk protein in the ovaries, 43 and the silencing of the VgR gene extended the pre-ovipositional period and reduced the egg number and fertility in H. axyridis and Cadra cautella. 43,44 In Sogatella furcifera, the knockdown of SfVg and SfVgR reduced vitellin levels in the basal oocyte and resulted in the production of few or no complete oocytes. 45 Finally, previous studies in B. dorsalis showed that the down-regulation of BdVg and BdVgR disrupts ovarian growth, reduces ovary size and limits egg production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Similarly, the RNAi-mediated silencing of HmVgR blocked the deposition of yolk protein in the ovaries, 43 and the silencing of the VgR gene extended the pre-ovipositional period and reduced the egg number and fertility in H. axyridis and Cadra cautella. 43,44 In Sogatella furcifera, the knockdown of SfVg and SfVgR reduced vitellin levels in the basal oocyte and resulted in the production of few or no complete oocytes. 45 Finally, previous studies in B. dorsalis showed that the down-regulation of BdVg and BdVgR disrupts ovarian growth, reduces ovary size and limits egg production.…”
Section: Discussionmentioning
confidence: 99%
“…In Corcyra cephalonica , the ovaries of females injected with CceVg double‐stranded RNA (dsRNA) were severely deformed, with short ovarioles, unordered egg sizes and few fully developed eggs 42 . Similarly, the RNAi‐mediated silencing of HmVgR blocked the deposition of yolk protein in the ovaries, 43 and the silencing of the VgR gene extended the pre‐ovipositional period and reduced the egg number and fertility in H. axyridis and Cadra cautella 43,44 . In Sogatella furcifera , the knockdown of SfVg and SfVgR reduced vitellin levels in the basal oocyte and resulted in the production of few or no complete oocytes 45 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to that of S. litura and Chilo suppressalis (Walker) (Lepidoptera: Crambidae); that is, the expression of Vg and VgR can be first detected at the end of the pupa stage and increases rapidly in the adult stage [ 11 , 35 , 43 ]. The expression of Vg and VgR usually has a similar trend, and this expression pattern is closely related to the process of vitellogenesis and the state of ovarian development [ 3 , 44 ]. Thus, the expression of Vg and VgR could become new targets for forecasting the occurrence of pests in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae), silencing RfVg extended the preoviposition period, reduced egg quantity, significantly lowered egg viability, and induced alterations in egg and ovary phenotypes (Rasool et al, 2021). In the ladybird Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), ds HaVgR ‐induced silencing led to a reduction in ovary size, an increase in the preoviposition period, and a decrease in the number of eggs (Han, Han, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%